20 ways to draw a cat and 44 other awesome animals : a sketchbook for artists, designers, and doodlers - Kuo, Julia (20 Ways Ser., 2013)
This inspiring sketchbook is part of the new 20 Ways series from Quarry Books, designed to offer artists, designers, and doodlers a fun and sophisticated collection of illustration fun. Each spread features 20 inspiring illustrated examples of a single animal, such as a cat, giraffe, seal, elephant, or whale-with blank space for you to draw your take on "20 Ways to Draw a Cat."This is not a step-by-step technique book--rather, the stylized animals are simplified, modernized, and reduced to the most basic elements, showing you how simple abstract shapes and forms meld to create the building blo.